The Evolution and the Advantages of MicroED - Nannenga, Brent L.; Bu, Guanhong; Shi, Dan (Frontiers in Molecular Biosciences, 2018)
MicroED is a method which combines cryo-EM sample preparation and instrumentation, with electron and X-ray crystallography data analysis, and it has been employed to solve many protein crystal structures at high resolution. Initially, the main doubts of this method for structure determination were the dynamic scattering of electrons, which would cause severe inaccuracies in the measured intensities. In this paper, we will review the evolution of MicroED data collection and processing, the major differences of multiple scattering effects in protein crystals and inorganic material, and the advantages of continuous rotation data collection. Additionally, because of the periodic nature of the crystalline sample, radiation doses can be kept significantly lower than those used in single particle data collection. We review the work where this was used to assess the radiation damage of a high-energy electron beam on the protein molecules at much lower dose ranges compared to imaging.